Network knowledge gathering of international new ventures, approaches, and preconditions - Lidia Danik; Izabela Kowalik (International Journal of Management and Economics, 2020)
This paper contributes to the growing stream of research on knowledge gathering in the internationalization process of international new ventures (INVs), as well as their networking activities. It identifies two dimensions describing the network knowledge-gathering approaches: 1) relationship approach (well-wishing or opportunistic) and 2) intentionality (intentional or unintentional search for knowledge), which enable the classification of the INV activities. The findings are based on a qualitative study conducted on four Polish INVs from the manufacturing industry. They show that internationalizing companies may behave opportunistically in their knowledge-gathering behavior, while, at the same time, some of their knowledge is also gathered unintentionally. The preconditions of knowledge-gathering behaviors suggested in the study include, among others, the managers' experience, power division in the networks, and the duration of a relationship with a partner.
Keywords: D83; F23; 650; knowledge gathering; organizational learning; international new ventures; network internationalization; opportunism; Central and Eastern European Countries